Measurement and analysis of fatigue crack deformation at the micro-scale (Fracture and Structural Integrity, 2017)
This paper introduces the use of digital image correlation for the measurement of surface displacements in the neighbourhood of a crack tip, both at the macro- and micro- scale. Various methods of interpreting the measured data and producing a crack driving force are then discussed, including the use of the full CJP model. A reduced set of parameters are then proposed, corresponding to the three principal interaction forces between the plastic enclave and the surrounding elastic material. Our own results, and those of Vasco Olmo, previously reported in the literature are then reanalysed using this new framework, and excellent agreement between two independent experiments is obtained. Implications for the analysis of further data sets are then discussed.
Keywords: Fatigue; Crack Driving Force; Digital Image Correlation; CJP model